(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The article analyzes the prevalence of helminthiasis in the world. Particular attention is paid to the phase of pathogenesis and clinical manifestations of helminthiases. The most important role in helminthiasis is revealed - the factor of the helminth’s influence on the host’s immune system.